Pengembangan Pocket Book Fisika Berbasis Problem Based Learning untuk Meningkatkan Pemahaman Konsep Fisika Kelas XI - Ahmad, Emma Zulfiana; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2020)
This study aims to determine the characteristics, feasibility, and effectiveness of the use of physics pocket books that were developed to improve students' conceptual understanding. This study uses the research and development method or Research and Development (R & D) with the research design used is one group pretest-posttest design. The test subjects of this study were students of class XI MIPA II and the initial trials of students were class XII MIPA I at SMA Negeri 12 Semarang.. The stages of this research are definition, design, and development. The research data were collected using a questionnaire, concept understanding test, interview guide sheets, and documentation. Concept understanding test in the form of pretest-posttest questions. Questionnaires and questions were given before and after using the physics pocket book based on problem based learning. Data analysis using Likert scale, n-gain and t test. The pocket book that has been developed is then tested for feasibility using a feasibility test questionnaire filled out by a validator and then a development trial is carried out in learning activities. The physics problem-based learning pocket book has four characteristics, namely comic stories, material descriptions, discussion activities, and is equipped with sample questions and practice questions. The results of the feasibility test questionnaire showed an average assessment score of 79.80% which was included in the feasible criteria. Based on this test, it can be said that the problem-based learning physics pocket book is feasible to be used as an alternative learning medium in the learning process. Furthermore, from the n-gain test for each indicator of competency achievement and each indicator of concept understanding, it is included in the moderate criteria of 0.5737 and 0.5823. Meanwhile, the t test results are t count> t table of 24.8994> 2.0301. Thus, overall it can be concluded that the use of problem-based learning physics pocket books can improve students' conceptual understanding.